Efficient Hydrogen Delivery for Microbial Electrosynthesis via 3D-Printed Cathodes - Kracke, Frauke; Deutzmann, Jörg S.; Jayathilake, Buddhinie S.; Pang, Simon H.; Chandrasekaran, Swetha; Baker, Sarah E.; Spormann, Alfred M. (Frontiers in Microbiology, 2021)
The efficient delivery of electrochemically in situ produced H2 can be a key advantage of microbial electrosynthesis over traditional gas fermentation. However, the technical details on how to supply large amounts of electric current per volume in a biocompatible manner remain unresolved. Here, we explored for the first time the flexibility of complex 3D-printed custom electrodes to fine-tune H2 delivery during microbial electrosynthesis. Using a model system for H2-mediated electromethanogenesis comprised of 3D fabricated carbon aerogel cathodes plated with nickel-molybdenum and Methanococcus maripaludis, we showed that novel 3D-printed cathodes facilitated sustained and efficient electromethanogenesis from electricity and CO2 at an unprecedented volumetric production rate of 2.2 LCH4 /Lcatholyte/day and at a coulombic efficiency of 99%. Importantly, our experiments revealed that the efficiency of this process strongly depends on the current density. At identical total current supplied, larger surface area cathodes enabled higher methane production and minimized escape of H2. Specifically, low current density (< 1 mA/cm2) enabled by high surface area cathodes was found to be critical for fast start-up times of the microbial culture, stable steady state performance and high coulombic efficiencies. Our data demonstrate that 3D-printing of electrodes presents a promising design tool to mitigate effects of bubble formation and local pH gradients within the boundary layer and, thus, resolve key critical limitations for in situ electron delivery in microbial electrosynthesis.